2020
DOI: 10.1177/1120672120936175
|View full text |Cite
|
Sign up to set email alerts
|

Valsalva retinopathy: Long-term results and management strategies

Abstract: Purpose: To investigate the long-term results and efficacy of the treatment modalities for preretinal hemorrhage due to valsalva retinopathy. Methods: Retrospective review was conducted on 24 eyes of 24 patients with valsalva retinopathy who were treated between 2004 and 2019. These patients were treated with Nd:YAG laser, argon laser and vitrectomy or were only observed. Nd:YAG laser hyaloidotomy was performed in 10 eyes, argon laser was applied to two of those following failed Nd:YAG laser, and vitrectomy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Celik Dulger et al reported that a PMH ≤1DD in size resolved spontaneously within 2–3 months, while hemorrhages 1–4DD in size took nearly 6 months for complete resolution. 10 While most authors prefer to manage PMH ≤3DD size conservatively, some prefer to treat even the smaller hemorrhages. 116…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Celik Dulger et al reported that a PMH ≤1DD in size resolved spontaneously within 2–3 months, while hemorrhages 1–4DD in size took nearly 6 months for complete resolution. 10 While most authors prefer to manage PMH ≤3DD size conservatively, some prefer to treat even the smaller hemorrhages. 116…”
Section: Discussionmentioning
confidence: 99%
“…Pre-macular hemorrhage (PMH) is one of the rare causes of sudden painless profound visual loss. [1][2][3][4][5][6][7][8][9][10][11] It is associated with conditions like Valsalva retinopathy, retinal artery macroaneurysm (RAM), proliferative diabetic retinopathy, retinal vein occlusion (RVO), Terson's syndrome, and hematological disorders like aplastic anemia and leukemia. It presents as a circumscribed, boat-shaped, collection of blood located beneath the internal limiting membrane (ILM) and/ or between the ILM and the posterior hyaloid face.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the hemorrhage may regress spontaneously, it exposes to a risk of secondary preretinal fibrosis [ 21 ]. A slowly resolving subhyaloid hemorrhage also prolongs the contact of the retina with hemoglobin and iron, potentially leading to toxic damage to the retina, which can cause permanent visual loss [ 22 ].…”
Section: Clinical Discussionmentioning
confidence: 99%